Combating violent extremism and radicalization in the digital era - Khader, Majeed (Advances in religious and cultural studies (ARCS) book series, 2016)
"This book is an essential reference for the latest research on the utilization of online tools by terrorist organizations to communicate with and recruit potential extremists and examines effective countermeasures employed by law enforcement agencies to defend against such threats"--